IMPLEMENTATION OF DIFFERENTIATED LEARNING IN ANECDOTAL TEXT WRITING SKILLS: A CASE STUDY IN VOCATIONAL SCHOOLS - Zeny Arisa Alfiyah Rofi; Andayani; Budhi Setiawan (SOSIOEDUKASI, 2025)
Differentiated learning is learning that accommodates students' differences in learning activities in line with readiness, interests, talents, and learning styles. This study aims to describe the planning and implementation of differentiated learning in class X anecdotal text writing skills at SMK Sakti Gemolong. This research uses a descriptive qualitative method through a case study approach. Data sources are in the form of learning events and activities in the classroom, informants of Indonesian teachers and students, and documents. Sampling was done using purposive sampling. Data collection techniques are obtained through observation, interviews, and document analysis. Data validity by tracing sources and methods. Data analysis using interactive models. The result of the research is that the learning plan has been fulfilled conceptually. However, the implementation of learning has inconsistencies with planning, especially the differentiation of content, processes, and products.  Meanwhile, assessments have included diagnostic, formative, and summative assessments, although they have not been optimally applied in differentiated learning in anecdotal text writing skills.